Triphasic scaffolds for the regeneration of the bone–ligament interface. (29th January 2016) - Criscenti, G; Longoni, A; Di Luca, A; De Maria, C; van Blitterswijk, C A; Vozzi, G; Moroni, L
Abstract: A triphasic scaffold (TPS) for the regeneration of the bone–ligament interface was fabricated combining a 3D fiber deposited polycaprolactone structure and a polylactic co-glycolic acid electrospun. The scaffold presented a gradient of physical and mechanical properties which elicited different biological responses from human mesenchymal stem cells. Biological test were performed on the whole TPS and on scaffolds comprised of each single part of the TPS, considered as the controls. The TPS showed an increase of the metabolic activity with culturing time that seemed to be an average of the controls at each time point. The importance of differentiation media for bone and ligament regeneration was further investigated. Metabolic activity analysis on the different areas of the TPS showed a similar trend after 7 days in both differentiation media. Total alkaline phosphatase (ALP) activity analysis showed a statistically higher activity of the TPS in mineralization medium compared to the controls. A different glycosaminoglycans amount between the TPS and its controls was detected, displaying a similar trend with respect to ALP activity. Results clearly indicated that the integration of electrospinning and additive manufacturing represents a promising approach for the fabrication of scaffolds for the regeneration of tissue interfaces, such as the bone-to-ligament one, because it allows mimicking the structural environment combining different biomaterials at different scales.